Investigating Wind Direction Influence on Wind-Generated Waves Using Delft 3D for Gaza Strip Coast - Alqatanani, Anass; Yeter GÜNAL, Ayşe; AL ASTA, M.SOBHI; Jaroun, Abdallah; Al-Masri, Adnan (Iraqi Journal of Civil Engineering, 2022)
Wind and water levels influence wave overtopping and consequent coastal flood threat, which is especially important in hyper-tidal bays where even modest variations in wave heights may be devastating if they coincide with high tides. The influence of wind and wave characteristics on wave propagation, as well as the sensitivity of significant wave height, are numerically investigated along the Gaza Strip's beachfront as an example. Wind waves with a high amplitude and short duration are susceptible to opposing winds, and their steepening effect varies throughout the bay shoreline, underlining the impact of shoreline geometry and bathymetry on wave hazard. The findings contribute to our existing knowledge of the complex interplay between wind and waves, as well as the crucial variables that maximize danger and hazard variability along the coastline. The findings of this study can assist port and harbor managers prevent financial losses due to downtime, influence sustainable coastal sea defense design, and better understand how wave danger may change in the future owing to shifting storm tracks. The findings can also be used to improve coastal infrastructure design and disaster response planning. Two scenarios were investigated with a wind direction of 330 and 30. It seems that when the wind direction is 330, it produces a higher Hs of 1.2 m and relatively larger wave return period with a range of 12-22 s and a higher wave energy dissipation of 220 N/Ms. In contrast, when the wind direction is 30, it produces a smaller HS of 1m with a short wave return period of 15-17s and smaller wave energy dissipation of 120 N/Ms. Overall, a wind direction of 30 has fewer occurring chances over the year but it seems to produce a destructive wave that are spread over the whole coast with a rapid return period.